Neural correlates of distraction in borderline personality disorder before and after dialectical behavior therapy - Winter, Dorina; Bohus, Martin; Schmahl, Christian; Herpertz, Sabine (European archives of psychiatry and clinical neuroscience, 2017)
Neural underpinnings of emotion dysregulation in borderline personality disorder (BPD) are characterized by limbic hyperactivity and disturbed prefrontal activity. It is unknown whether neural correlates of emotion regulation change after a psychotherapy which has the goal to improve emotion dysregulation in BPD, such as dialectical behavioral therapy (DBT). We investigated distraction as a main emotion regulation strategy before and after DBT in female patients with BPD. Thirty-one BPD patients were instructed to either passively view or memorize letters before being confronted with negative or neutral pictures in a distraction task during functional magnetic resonance imaging. This paradigm was applied before and after a 12-week residential DBT-based treatment program. We compared the DBT group to 15 BPD control patients, who continued their usual, non-DBT-based treatment or did not have any treatment, and 22 healthy participants. Behaviorally, BPD groups and healthy participants did not differ significantly with respect to alterations over time. On the neural level, BPD patients who received DBT-based treatment showed an activity decrease in the right inferior parietal lobe/supramarginal gyrus during distraction from negative rather than neutral stimuli when compared to both control groups. This decrease was correlated with improvement in self-reported borderline symptom severity. DBT responders exhibited decreased right perigenual anterior cingulate activity when viewing negative (rather than neutral) pictures. In conclusion, our findings reveal changes in neural activity associated with distraction during emotion processing after DBT in patients with BPD. These changes point to lower emotional susceptibility during distraction after BPD symptom improvement.